(untitled) (Modern American Journal of Social Sciences and Humanities, 2026)
This article is devoted to the analysis of the story “The Woman Who Did Not Eat Raisins” by Abdulla Khahhor, a great figure of Uzbek literature. The article highlights the writer’s ability to expose the ignorance in society and the two-sided way of life of people by means of sharp social irony, simple and vital language, as well as deep psychological imagery.